Inorganic-organic core-shell titania nanoparticles for efficient visible light activated photocatalysis - Moustakas, N.G.; A. G. Kontos; V. Likodimos; Katsaros, F.; N. Boukos; Tsoutsou, D.; Dimoulas, A.; Romanos, G.E.; Dionysiou, D.D.; P. Falaras (Applied Catalysis B: Environmental, 2013)
Nanostructured modified TiO2 (m-TiO2) was synthesized using the gel combustion method based on the calcination of an acidified alkoxide solution mixed with urea. The materials were characterized by Raman, FT-IR and UV-vis diffuse reflectance spectroscopies, transmission (TEM) and scanning electron microscopies (SEM), X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR), in comparison with reference material untreated with urea (ref-TiO2). The effect of both the urea content and calcination temperature were optimized, providing the optimal absorption threshold of 2.19eV for solar light harvesting. The photocatalytic performance of the m-TiO2 powder was tested for the degradation of methylene blue (MB) azo dye under UVA (350-365nm), visible (440-460nm), and daylight (350-750nm) illumination. The hybrid inorganic/organic material shows exceptional physicochemical properties and significant photocatalytic activity, especially in the visible, attributed to sensitization of the TiO2 by a thin porous layer of carbonacious species in controlled core-shell morphology. © 2012 Elsevier B.V.